2014
DOI: 10.1016/j.ejso.2014.02.225
|View full text |Cite
|
Sign up to set email alerts
|

Real-time intraoperative detection of breast cancer using near-infrared fluorescence imaging and Methylene Blue

Abstract: Background Despite recent developments in preoperative breast cancer imaging, intraoperative localization of tumor tissue can be challenging, resulting in tumor-positive resection margins during breast-conserving surgery. Based on certain physicochemical similarities between Technetium(99mTc)-sestamibi (MIBI), a SPECT radiodiagnostic with a sensitivity of 83–90% to detect breast cancer preoperatively, and the near-infrared (NIR) fluorophore Methylene Blue (MB), we hypothesized that MB might detect breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
121
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 30 publications
0
121
0
Order By: Relevance
“…This study enabled identification of 20 out of 24 cancers (21 were invasive and three were in situ) within the resected specimens using the near-infrared fluorescence imaging. 67 Therefore, this technique clearly has the potential to enable margin assessment intra-operatively, but remains at an early stage of development.…”
Section: Magnetically Guided Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study enabled identification of 20 out of 24 cancers (21 were invasive and three were in situ) within the resected specimens using the near-infrared fluorescence imaging. 67 Therefore, this technique clearly has the potential to enable margin assessment intra-operatively, but remains at an early stage of development.…”
Section: Magnetically Guided Localizationmentioning
confidence: 99%
“…67 In a small feasibility study in 24 patients with invasive breast cancer, methylene blue was administered intravenously within 3 h of surgery. 67 A fluorescence-assisted resection and exploration imaging system (mini-FLARE™, FLARE Foundation, USA) was used to identify the fluorescent signal during surgery and within excised specimens. This study enabled identification of 20 out of 24 cancers (21 were invasive and three were in situ) within the resected specimens using the near-infrared fluorescence imaging.…”
Section: Magnetically Guided Localizationmentioning
confidence: 99%
“…Non-targeted agents provide contrast due general properties of tumors, rather than presence of a specific antigen, and they include unconjugated fluorescent dyes and a subset of nanoparticles. Unconjugated fluorescent dyes such as fluorescein [23], methylene blue [24], or indocyanine green [23, 25] can be delivered locally or systemically, and accumulate in areas of tumor tissue that have disrupted or altered tumor vasculature and drainage.…”
Section: Non-targeted Imaging Agentsmentioning
confidence: 99%
“…Methylene blue is a third clinically available imaging agent that has been tested for its ability to label tumor tissues. Tummers et al reported a study in which patients with breast cancer patients were administered intravenous methylene blue prior to tumor resection, and subsequent fluorescence imaging of the resected tissue showed a tumor to background fluorescence ratio of 2.4 (28). Nonspecific fluorescent contrast agents provide one reasonable option for intraoperative imaging as they are clinically available.…”
Section: Optical Imagingmentioning
confidence: 99%